2021
DOI: 10.47602/jpsp.v6i1.262
|View full text |Cite
|
Sign up to set email alerts
|

Exploring academic and character strengths in students with sex chromosome aneuploidies

Abstract: Children with sex chromosome aneuploidies (SCAs) are often characterized in the literature by limitations and pathologies related to the genetic diagnosis. This study aimed to broaden the SCA phenotype by describing parent reported character and academic strengths. Parents of children with SCAs ages 3-21 (N=377) responded to an electronic survey asking them to describe their child’s strengths in academic settings. Responses were coded for strengths-based content and analyzed using a mixed-methods content analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Academic difficulties among individuals with XYY are common, and individuals often receive special education (Geerts et al 2003 ; Linden and Bender 2002 ). However, it should be noted that individuals with XYY possess other strengths in the academic setting, such as curiosity, humor, and teamwork (Thompson et al 2022 ). Additionally, individuals were reported to possess strengths in the areas of science, technology, engineering, and mathematics (Linden and Bender 2002 ; Thompson et al 2022 ).…”
Section: Neurodevelopmental Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Academic difficulties among individuals with XYY are common, and individuals often receive special education (Geerts et al 2003 ; Linden and Bender 2002 ). However, it should be noted that individuals with XYY possess other strengths in the academic setting, such as curiosity, humor, and teamwork (Thompson et al 2022 ). Additionally, individuals were reported to possess strengths in the areas of science, technology, engineering, and mathematics (Linden and Bender 2002 ; Thompson et al 2022 ).…”
Section: Neurodevelopmental Featuresmentioning
confidence: 99%
“…While early intervention and multidisciplinary care are key to improving outcomes in children with XYY, a recent study also described the importance of interventions that highlight the strengths of children with XYY rather than solely targeting deficits (Thompson et al 2022 ). With respect to academic support, strengths-based approaches have been shown to improve student wellbeing, aid academic achievement, and build student capacity (Thompson et al 2022 ).…”
Section: Management Recommendations and Multidisciplinary Carementioning
confidence: 99%
See 1 more Smart Citation
“…Parents strongly desire a balanced presentation of both positive and negative aspects of the condition [ 26 ]. While the literature has historically been focused on symptom characterization, studies are beginning to highlight relative strengths of children and individuals with these conditions, including kindness, honesty, being eager to please, and love of learning [ 57 , 58 ], which can be contextualized in reference to the parent–child relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Noticing student assets and providing students with opportunities to utilize and share their strengths in the school setting may contribute to overall student well‐being. Prior studies have shown children with SCAs are prone to exceptional kindness, an eagerness to please, creative thinking and perseverance (Thompson et al., 2022). Finally, many students with SCAs will not have the option to attend the specialized schools with small class sizes and modified curriculum that some of our participants reported as beneficial.…”
Section: Discussionmentioning
confidence: 99%